2016
DOI: 10.1016/j.jvs.2015.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behavior is associated with impaired biomarkers in claudicants

Abstract: Objective Time spent in sedentary behavior has been associated with worse inflammation and cardio-metabolic biomarkers in various populations. However, the association between time spent in sedentary behavior and biomarkers remains unknown in intermittent claudication patients. The aim of the current study was to analyze the relationship between sedentary behavior and inflammatory and cardio-metabolic biomarkers in patients with symptomatic peripheral artery disease (PAD). Methods The sample included 297 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
1
17
1
Order By: Relevance
“…residents of metropolitan cities) recruited from the database of studies developed and published before the COVID-19 pandemic by our group. 1 , 3 , 4 , 5 , 11 , 12 , 13 This study was approved by the Universidade Nove de Julho’ Ethics Committee before data collection (CAAE #31529220.8.0000.5511). All participants verbally gave informed consent by phone prior to participation.…”
Section: Methodsmentioning
confidence: 99%
“…residents of metropolitan cities) recruited from the database of studies developed and published before the COVID-19 pandemic by our group. 1 , 3 , 4 , 5 , 11 , 12 , 13 This study was approved by the Universidade Nove de Julho’ Ethics Committee before data collection (CAAE #31529220.8.0000.5511). All participants verbally gave informed consent by phone prior to participation.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in non-PAD subjects showed that sedentary behavior is associated with fatal and nonfatal cardiovascular disease, and all-cause mortality independent of physical activity level 11, 12 . In patients with symptomatic PAD, sedentary behavior was associated with worse inflammation, coagulation, glucose, and lipid profiles 13 and greater functional decline 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Only two previous studies explored the association between hemostatic markers and SB through objective assessment, in older men [20] and patients with symptoms of peripheral arterial disease [21]. In the study of Farah et al, SB remained associated with fibrinogen after adjustment for sex, age, PA status, BMI, and severity of peripheral arterial disease [21]. Parsons et al found an association between sedentary time and some fibrinolytic markers but they did not assess fibrinogen [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in these researches, neither PA nor SB were objectively assessed. Only two studies explored the association between inflammatory/hemostatic markers and objectively assessed SB, in older men [20] and patients with intermittent claudication [21]. We sought to explore the correlation between objectively measured SB and circulating fibrinogen levels in postmenopausal women, a population particularly susceptible to increase the risk of CVD due to changes in hemostatic parameters [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%